2016
DOI: 10.4172/1948-5948.1000286
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Trichoderma spp. by DNA Barcode and Screening for Cellulolytic Activity

Abstract: J o u rn al of M ic ro b ia l & Bioc h e m ic a l Te chno lo g y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…Species of the Trichoderma genus are typically found as soil-borne or wood-decaying fungi. Some species are economically important because they produce industrial enzymes (cellulase and hemicellulase) and antibiotics or act as biocontrol agents (Hassan 2014 andFahmi et al 2016). Therefore, correct identification of Trichoderma at the species level is important.…”
Section: Sequencing Of Its Regionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Species of the Trichoderma genus are typically found as soil-borne or wood-decaying fungi. Some species are economically important because they produce industrial enzymes (cellulase and hemicellulase) and antibiotics or act as biocontrol agents (Hassan 2014 andFahmi et al 2016). Therefore, correct identification of Trichoderma at the species level is important.…”
Section: Sequencing Of Its Regionsmentioning
confidence: 99%
“…Many other researchers have used ITS sequences to identify Trichoderma spp. (Rifai 1969 andFahmi et al 2016). Multiple alignment of the ITS sequences of all seven Trichoderma species identified nucleotide sequence differences for differentiating these species.…”
Section: Phylogenetic Analysis Of the Its Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to the production of diffusible components, such as lytic enzymes or water-soluble metabolites. These components, such as chitinase, protease and glucanase, were always secreted by Trichoderma at low concentration [5,25]. Therefore, they can act against the pathogenic fungi before mycelial contact, thus increasing the antagonism of Trichoderma.…”
Section: Antagonistic Activity Of Fusants In Dual Culture Techniquementioning
confidence: 99%
“…to be applied in the field of biological control is an important issue. It was reported that identification of Trichoderma based on morphological characters can give misleading results (Fahmi et al, 2016). Recently, molecular identification based on internal transcribed spacers (ITS) amplification and sequencing is common and highly trusted (Savitha and Sriam, 2015;Fahmi et al, 2016;Oskiera et al, 2015;Jiang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%